1976
DOI: 10.1097/00000658-197604000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Hematuria and Rectal Bleeding in the Child with Klippel and Trenaunay Syndrome

Abstract: We have operated upon 588 patients with Klippel and Trenaunay syndrome. The underlying factor is a congenital malformation of the deep veins: agenesis, atresia or compression by fibrovascular bands of the popliteal, femoral or iliac veins. Of these 588 patients, 6 children between 15 months and 4 years of age had severe rectal bleeding and hematuria. One of these children died from massive bleeding of the rectum with septicemia. Another boy was saved by rectal resection and the last one by subtotal cystectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 0 publications
0
52
0
1
Order By: Relevance
“…Gastrointestinal hemorrhage usually presents in the first decade of the patient's life and tends to be intermittent. 5 In the present case, the patient had suffered from recurrent hematochezia for several years and was diagnosed with rectal varix and iron deficiency anemia. In general, hematochezia may be caused by the posterior or compensatory venous pathways of the extremity, which drain into the internal vein.…”
Section: Case Reportmentioning
confidence: 73%
See 1 more Smart Citation
“…Gastrointestinal hemorrhage usually presents in the first decade of the patient's life and tends to be intermittent. 5 In the present case, the patient had suffered from recurrent hematochezia for several years and was diagnosed with rectal varix and iron deficiency anemia. In general, hematochezia may be caused by the posterior or compensatory venous pathways of the extremity, which drain into the internal vein.…”
Section: Case Reportmentioning
confidence: 73%
“…2 The most common involvement in the gastrointestinal tract is diffuse cavernous hemangiomas of the distal colon and the rectum. 5,6 In one of the largest published studies of KTS patients, hematochezia was observed in six of the 588 patients. 3 Although rare, bleeding from jejunal hemangiomas and esophageal and gastric varices also have been reported.…”
Section: Case Reportmentioning
confidence: 99%
“…Hematuria is a common symptom in patients with genitourinary and pelvic vascular malformation necessitating therapeutic intervention. Hematuria as a presenting symptom has been reported in children [1][2][3], but massive hematuria in adults associated with KTS is rare [7][8][9]. We report 2 cases of hematuria in adults with KTS.…”
Section: Introductionmentioning
confidence: 84%
“…Although the lower extremity is involved in the majority of cases [1], pelvic vascular involvement appears to be responsible for rectal bleeding and hematuria in children with this syndrome [3]. Both hemangioma and vascular malformations have been reported [1][2][3]. Hemangiomas are true benign tumors characterized by proliferating endothelial cells while congenital vascular malformations are defects of vascular morphogenesis which tend to be diffuse [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation